2008
DOI: 10.1111/j.1600-0722.2008.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of SIBLING proteins in the organic and inorganic phases of rat dentin and bone

Abstract: The SIBLING protein family is a group of non-collagenous proteins (NCPs) that includes dentin sialophosphoprotein (DSPP), dentin matrix protein 1 (DMP1), bone sialoprotein (BSP), and osteopontin (OPN). In the present study, we compared these four proteins in different phases of rat dentin and bone. First, we extracted NCPs in the unmineralized matrices and cellular compartments using guanidium-HCl (G1). Second, we extracted NCPs closely associated with hydroxyapatite using an EDTA solution (E). Last, we extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 50 publications
3
111
0
2
Order By: Relevance
“…19 Since these NCPs are acidic and are secreted into the ECM during bone formation and mineralization, they are believed to play key biological roles in initiating and modulating the mineralization of collagen fibers when osteoids are converted into bone. 24 A number of studies have shown that mutation in or knocked out of genes coding for certain NCPs is associated with phenotypic abnormalities in bone mineralization. 22,[33][34][35] However, the way these NPCs in 3D scaffolds affect osteoblast response during bone tissue regeneration is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Since these NCPs are acidic and are secreted into the ECM during bone formation and mineralization, they are believed to play key biological roles in initiating and modulating the mineralization of collagen fibers when osteoids are converted into bone. 24 A number of studies have shown that mutation in or knocked out of genes coding for certain NCPs is associated with phenotypic abnormalities in bone mineralization. 22,[33][34][35] However, the way these NPCs in 3D scaffolds affect osteoblast response during bone tissue regeneration is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of OPN, DMP1, and BSP was confirmed by western blot analyses using specific antibodies. 24 …”
Section: Extraction Of Ncpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monoclonal anti-FAM20C antibodies (clone 3 or clone 5) were used at a dilution of 25 g of IgG/ml. A polyclonal biglycan antibody (LF-159) was used as described previously (13) as well as antibodies against bone sialoprotein (BSP), dentin sialoprotein (DSP; the N-terminal fragment of DSPP), and DMP1 (14,15). A polyclonal antibody against ameloblastin (Santa Cruz Biotechnology, Inc.) was employed following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The NCPs were extracted from the long bones of 4-wk-old mice (8 WT vs. 12 KO) with 4 M guanidine-hydrochloride/0.5 M EDTA containing protease and phosphatase inhibitors, followed by buffer exchange into 6 M urea (29). After they were dialyzed against water, the NCP samples (0.06 mg of each) were hydrolyzed in 0.2 M NaOH, and the concentration of inorganic phosphate (P i ) liberated from the phosphoproteins was determined (6,(30)(31)(32).…”
Section: Extraction Of Bone Ncps and Measurement Of Attached Phosphatesmentioning
confidence: 99%